2019
DOI: 10.1177/0265407519847772
|View full text |Cite
|
Sign up to set email alerts
|

The color continuum: Skin tone and online dating preferences among Asian Americans

Abstract: Despite the increasing body of literature surrounding online dating preferences, there remains a paucity of research that analyzes whether skin color influences the dating selection process. To fill this empirical gap, the present study uses data collected from 2,024 Asian dating profiles, including the skin tone of the daters, to assess the impact that skin color variation may have on the inter- and intraracial dating preferences of heterosexual males and females as well as gay males and lesbians. This resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The second of the four factors that aligned more consistently with one of our three hypothesized domains was the Asian Americans as Desirable subscale. The presence of this factor aligns with the burgeoning research literature surrounding how both dating preferences and preferences related to physical attractiveness are indeed racialized (Tsunokai et al, 2014(Tsunokai et al, , 2019, in contrast with color-blind ideologies that attraction is race neutral (Eastwick et al, 2009). More specifically, our study suggests that an increased view of fellow Asian Americans as desirable is positively correlated with collective self-esteem and negatively correlated with internalized racist appearance bias, highlighting how positive feelings about one's own racial group and identity are associated with the extent to which one feels attracted to members of one's racial group.…”
Section: Pride In Asian American Appearancesupporting
confidence: 59%
See 1 more Smart Citation
“…The second of the four factors that aligned more consistently with one of our three hypothesized domains was the Asian Americans as Desirable subscale. The presence of this factor aligns with the burgeoning research literature surrounding how both dating preferences and preferences related to physical attractiveness are indeed racialized (Tsunokai et al, 2014(Tsunokai et al, , 2019, in contrast with color-blind ideologies that attraction is race neutral (Eastwick et al, 2009). More specifically, our study suggests that an increased view of fellow Asian Americans as desirable is positively correlated with collective self-esteem and negatively correlated with internalized racist appearance bias, highlighting how positive feelings about one's own racial group and identity are associated with the extent to which one feels attracted to members of one's racial group.…”
Section: Pride In Asian American Appearancesupporting
confidence: 59%
“…Both Asian American heterosexual women and gay men express a greater interest in dating White partners over non-White partners, and even more specifically expressed less of a preference to date another Asian person compared to their heterosexual male counterparts (Tsunokai et al, 2014). Darker skinned Asian Americans report less of a desire to date fellow Asian individuals (Tsunokai et al, 2019). This perceived undesirability of one’s own racial group may stem both from the privileges given to those with lighter skin (Hunter, 2008; Rondilla & Spickard, 2007), as well as from how the media depicts Asian men as asexual and sexually undesirable, whereas Asian American women are portrayed as submissive, exotic, and sexually available to White men (Larson, 2006).…”
Section: Body Image Among Asian Americansmentioning
confidence: 99%
“…Based on previous literatures, the sociodemographic variables will be ascertained and selected a priori . These variables include age,83–87 sex at birth,88–90 sexual orientation,91–93 household income,90 94 working status,90 95 highest educational attainment,90 95 relationship status96 97 and type of residence 98 99…”
Section: Methods and Analysismentioning
confidence: 99%
“…However, this pattern does not hold across the Asian American diaspora. The few empirical studies that include queer Asian American women have found that their racial dating preferences are distinct from that of their racial peers (Rafalow et al 2017;Curington et al 2021;Tsunokai et al 2019). Queer Asian American women are more likely to state preferences for Asian partners over white partners on online dating sites (Rafalow et al 2017;Curington et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Queer Asian American women are more likely to state preferences for Asian partners over white partners on online dating sites (Rafalow et al 2017;Curington et al 2021). They are also more likely to both initiate messages to and reciprocate messages from Asian American women over white women on dating platforms and more open to dating African American and Latino partners (Tsunokai et al 2019). The instability of Asian American racial dating preferences suggests that assimilation might be mediated by the interaction between race, gender, and sexual orientation.…”
Section: Introductionmentioning
confidence: 99%